IMPLEMENTATION OF E-COMMODITY FOR FARMERS IN ORDER TO FACILITATE THE DISTRIBUTION OF CROPS IN SUKAPURA VILLAGE, KERTASARI DISTRICT, BANDUNG REGENCY - Hari Supriyadi; M. Rozahi Istambul; Ucu Nugraha; Parlindungan Parlindungan (Jurnal Darma Agung, 2022)
This research was conducted at the Vegetable Farmer Community in Sukapura Village, Kertasari District, Bandung Regency. This study aims to design a distribution system for agricultural products that involves elements of information technology in the form of designing an e-Commodity system. The e-Commodity system can be said to use internet technology to improve and change the main business processes, especially in terms of selling vegetable farm products. The e-Commodity system in addition to cutting distribution channels from farmers to consumers can also provide benefits in managing agricultural products. The approach method used in the distribution system of agricultural products that involves elements of information technology in the form of designing an e-Commodity system in the Vegetable Farmer Community in Sukapura Village, Kertasari District, Bandung Regency uses the Development Live Cycle System (SDLC) as a framework for designing a distribution system for agricultural products that involves information technology elements. The steps/stages are as follows: System Analysis and Design, Design, Application/Coding Development, Testing and Implementation, Maintenance. The findings of this study can be used as reference material in designing a distribution system for agricultural products that involves elements of information technology in the form of designing an e-Commodity system, this aims to collaborate between academia, industry and government in facilitating the distribution of agricultural products and increasing decent work and while at the same time increasing sustainable economic growth by designing and socializing the use of the e-Commodity System that can manage the distribution of agricultural products from upstream to downstream. This research is expected to be a reference in designing a distribution system for agricultural products that involves elements of information technology so that it is hoped that the existence of this e-Commodity System can provide convenience in the distribution of agricultural products and can have an impact on improving welfare for farmers.